Institucional isomorphism in IPSAS adoption - Rincón-Soto, Carlos Augusto; Gómez Villegas, Mauricio (Cuadernos de Administración, 2020)
The adoption of IPSAS is driven by various institutional factors that lead organizations to follow isomorphic behavior. Institutional isomorphism comes from various influences (coercive, mimetic, and normative), which could explain governments’ endorsement of this accounting model. This paper identifies and compares the factors and conditions that influence the adoption, adaptation, or non-adoption of IPSAS in different jurisdictions, from the institutional isomorphism perspective by using the systematic literature review methodology. Our findings account for the factors and conditions that isomorphically influenced IPSAS adoption or adaptation processes in various jurisdictions. Coercive isomorphism has been mostly driven by international institutions, while mimetic isomorphism is linked to governments’ search for trust. On the other hand, normative isomorphism has been related to the actions of political groups, public officials or professional institutions.